Development of Large Scale Microalgae Harvesting Method and Identification of Fatty Acids and Vitamin K from Dried Microalgae Cyclotella striata Biomass - PURWANTI (NIM : 10513018), IKE
One of the rapid and inexpensive method for harvesting microalgae in large scale is electroflotation. Electroflotation can separate microalgae cells from its culture by the formation of microbubbles resulting microalgae cells form flocs that floating on the surface of the culture. The aim of this study was to develop a method of harvesting microalgae biomass grown in large-scale outdoor photobioreactors and to identify fatty acids and vitamin K in the microalgae biomass. The research stages included preparation of microalgae biomass at indoor (from cultures 1 L to 240 L), production biomass in a 1500 L photobioreactor, designing and making of electroflotation modules, harvesting the biomass, isolation of the lipid from the biomass, analyzing fatty acid content and vitamin K. The microalgae that used in this study was Cyclotella striata. The results of harvesting trial of C. striata from 700 mL culture using electroflotation showed that C. striata cells were concentrated on the culture surface with a current density of 1.75 mA/cm 2, a measured voltage of 2 V for 10 min with an efficiency of 84%. For harvesting microalgae biomass in a large scale, a transparent chamber with a capacity of 200 L possessing 3 pairs of electrodes was elected. Applying 84 watts of power, 81 g of wet biomass was successfully separated from 200 L cultures within 10 min. So, the total energy required to harvest microalgae biomass from a 1500 L culture was 0.112 kWh. With assumption the electric cost of Rp 1467.28/kWh, the total cost for harvesting was Rp 0.18/kg biomass/L culture. Lipids extracted from C. striata biomass contained fatty acids and vitamin K. The content of saturated fatty acid, monounsaturated fatty acid, and polyunsaturated fatty acid in lipid C. striata was 31.17%; 64.63%; and 4.20% respectively.